Citizen-centric demand model for transformational government / Kamalia Azma Kamaruddin - Kamaruddin, Kamalia Azma (2018)
Transformational government (t-government) emerges from the evolution of electronic government (e-government) to become more citizen-focused while recognizing the need for fundamental changes of governance. Citizen-centric is a central concept being coined together with t-government implementation. Using t-government as a context, citizen-centricity is proposed as a remedial justification in solving e-government implementation issues. However, the question that remains is, how do we move a traditional agency-centric e-government to become a citizen-centric t-government? It has been found from the literatures that none of the research in e-government field has studied the characteristics of transformational government that addressed citizencentricity and modelled e-government services that described citizen-centric demand requirements. The knowledge gap on what constitutes citizen-centric demands of transformational government suggests that there is an impending need for a study to be conducted in this context. The aim of this study is to support the evolution of egovernment and complement transformational government by developing a model that address citizens' demands. Thus, this thesis makes modest theoretical, methodological and empirical contributions to the t-government phenomenon to identify the characteristics of transformational government that address citizen-centricity, model citizen-centric demand requirements for transformational government's online services and validate citizen-centric requirements model for transformational government's online services. The research sets out to produce a demand model that outlines the basic principles of citizen-centricity to implement transformational government online services. A qualitative approach is undertaken as the research attempts to establish elements of citizen-centric t-government and model citizen-centricity through interpretivism paradigm. To develop the model, this study has gone through an exploratory phase that involved two studies using literature analysis and experts' interview as its data collection methods, and thematic analysis for its data analysis method. Subsequently in the confirmatory phase, a multi-stakeholders interview has been conducted and model validation process has been performed using the criteria of importance and completeness. The result showed that, the constructs of Openness, Transparency, Participation and Responsiveness have been established as components of citizen-centric demand requirements that can benefit the supply side in conducting requirement gathering and designing of t-government online services. The findings can assist the governments, as a governing body in a state or country, to develop online services that fulfil citizens' needs thus increase satisfaction and trust to the government. The research has also provided theoretical, methodological and knowledge contributions to the field of e-government.